Decommissioned wind turbine blades: a pedagogical project on the uses of the raw material - Ribeiro, Luís Frölén (2018)
The incorporation of new technical challenges created by the increase of the wind power industry in the world and how they were integrated into a MSc Course of Mechanical Engineering is addressed in this article.